Phase variation and thermophysical properties of La2Hf2O7 with alumina addition. Issue 4 (April 2018) - Gu, Shengyue; Zhang, Shouyang; Xue, Bei; Yan, Jinkai; Li, Wei; Zhang, Leilei
Abstract: La2 O3 -Al2 O3 -HfO2 ceramics were prepared by solid reaction of La2 Hf2 O7 ceramic powders which were synthesized by solution combustion and commercial alumina powders at 1600 °C in air for 10 h. Phase variation and thermophysical properties of La2 O3 -Al2 O3 -HfO2 ceramics were investigated. With the increase of alumina content, LaAlO3, HfO2 and LaAl11 O18 phase structures appeared. The thermal expansion coefficients gradually increased with the increase of alumina content from 1000 °C to 1300 °C. The thermal conductivities of La2 O3 -Al2 O3 -HfO2 ceramics had nonlinear variation with the increase of alumina content and reached the lowest value around 1.1 W·m −1 ·K −1 when the ratio of La2 Hf2 O7 to Al2 O3 was 1:0.25. Therefore, the La2 O3 -Al2 O3 -HfO2 ceramics with a proper content of alumina can be considered as a new thermal barrier materials. Meanwhile, as potential application as interface layer in TBC, La2 O3 -Al2 O3 -HfO2 ceramics are beneficial to improve the effectiveness of the thermal barrier coating.